2018
DOI: 10.1016/j.neuron.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Organization of LRR Protein-Mediated Synaptic Adhesion Defines Synapse Identity

Abstract: Pyramidal neurons express rich repertoires of leucine-rich repeat (LRR)-containing adhesion molecules with similar synaptogenic activity in culture. The in vivo relevance of this molecular diversity is unclear. We show that hippocampal CA1 pyramidal neurons express multiple synaptogenic LRR proteins that differentially distribute to the major excitatory inputs on their apical dendrites. At Schaffer collateral (SC) inputs, FLRT2, LRRTM1, and Slitrk1 are postsynaptically localized and differentially regulate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 65 publications
(72 reference statements)
7
44
0
Order By: Relevance
“…The study characterizing Slitrk3 KO mice has further supported selective involvement of Slitrk3 in inhibitory synapse development (Takahashi et al, 2012 ) by detecting a decrease in inhibitory synapse number and function as well as seizure behaviors. On the other hand, RNAi-based knockdown studies as well as neuronal overexpression ones have indicated selective involvement of Slitrk1/2 in excitatory synapse number and function (Yim et al, 2013 ; Schroeder et al, 2018 ; Han et al, 2019 ). Also, Slitrk1 KO mice exhibit elevated anxiety behaviors (Katayama et al, 2010 ), and Slitrk5 KO mice display obsessive-compulsive–like behaviors with decreases in glutamate receptors and excitatory synaptic transmission in cortico-striatum synapses (Shmelkov et al, 2010 ).…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…The study characterizing Slitrk3 KO mice has further supported selective involvement of Slitrk3 in inhibitory synapse development (Takahashi et al, 2012 ) by detecting a decrease in inhibitory synapse number and function as well as seizure behaviors. On the other hand, RNAi-based knockdown studies as well as neuronal overexpression ones have indicated selective involvement of Slitrk1/2 in excitatory synapse number and function (Yim et al, 2013 ; Schroeder et al, 2018 ; Han et al, 2019 ). Also, Slitrk1 KO mice exhibit elevated anxiety behaviors (Katayama et al, 2010 ), and Slitrk5 KO mice display obsessive-compulsive–like behaviors with decreases in glutamate receptors and excitatory synaptic transmission in cortico-striatum synapses (Shmelkov et al, 2010 ).…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…Extracellular interactions of PTPσ with postsynaptic ligands could control the function of VGCCs (Muller et al, 2010). This hypothesis was supported by a study showing that KD of Slitrk1, a postsynaptic ligand for PTPσ, increased the number of docked SVs, 28 mimicking some of the loss-of-function phenotype of PTPσ cKO (Schroeder et al, 2018) (Fig 3).…”
Section: Ptpσ Requires Various Molecular Mechanisms To Regulate Excitmentioning
confidence: 68%
“…Although the current study focused on neuronal impairments, non-neuronal populations were also strongly affected by heroin and potentially contribute to addiction pathology. For example, SLITRK1, the most significantly altered gene in the non-neuronal population, is closely linked to synaptic plasticity 60 .…”
Section: Discussionmentioning
confidence: 99%